A Critical Review of Sitopaladi Churna in The Management of Respiratory Tract Infections: An Ayurvedic and Pharmacological Perspective - Kushwaha, Angad Kumar; Kumari, Sarita; Singh, Mahendra Prasad; Ranjan, Raman (Journal of Neonatal Surgery, 2025)
Respiratory tract infections (RTIs), including both upper and lower respiratory tract illnesses, continue to pose significant public health challenges across the globe. Conventional management largely depends on antibiotics, antihistamines, and corticosteroids, often leading to side effects and growing concerns regarding antimicrobial resistance. Ayurveda, the ancient Indian system of medicine, offers holistic and time-tested approaches to managing such conditions through formulations like Sitopaladi Churna. This classical polyherbal formulation is cited in authoritative Ayurvedic texts including Bhaishajya Ratnavali and Charaka Samhita, and has been used for centuries in treating Kasa (cough), Shwasa (dyspnoea), Jwara (fever), and Pratishyaya (rhinitis).Sitopaladi Churna consists of five key ingredients—Sitopala (sugar candy), Vanshlochan (Bambusa arundinacea), Pippali (Piper longum), Ela (Elettaria cardamomum), and Tvak (Cinnamomum zeylanicum)—each contributing specific Rasa, Guna, Veerya, and Vipaka attributes that enhance its efficacy. Modern pharmacological studies have shown that the formulation exhibits expectorant, bronchodilator, anti-inflammatory, immunomodulatory, and antimicrobial properties. Clinical studies have further validated its effectiveness in alleviating symptoms of RTIs, enhancing respiratory functions, and reducing dependency on synthetic drugs.This review critically explores the classical rationale, individual ingredient actions, formulation synergies, and recent scientific evidence pertaining to Sitopaladi Churna. It also discusses safety profiles and dosage considerations. Bridging traditional Ayurvedic insights with modern research findings, Sitopaladi Churna emerges as a safe, cost-effective, and promising formulation in the integrative management of respiratory tract infections.